(untitled) (Research, Society and Development, 2022)
The National Curricular Common Base brings in its text that the ultimate purpose of the Science area is the development of the capacity to act in and on the world, important for the full exercise of citizenship. Learning in this area of knowledge enables students to understand, explain and intervene in the world in which they live. The same area proves to be a great contribution to the challenge of preparing students to make responsible and conscious decisions in society. In this sense, this article brings up discussions on the relevance of Science for children in the formative phase, whose research objective was to understand the relevance and need to teach Natural Sciences in the Initial Years of Elementary School. Therefore, the research in question was based on a qualitative bibliographic research. Data analysis was performed according to Laurence Bardin’s content analysis assumptions. As a result, we can show that the area of Natural Sciences presents itself as a fundamental part of human survival and coexistence, since through their learning the child can come to understand the world that surrounds them and consciously intervene in it. However, this subject has gained a residual role within teaching with regard to the first school years, where it has been left in the background, giving priority to the areas of Mathematics and Languages.